Resistência e autonomia no discurso zapatista: “a nossa arma é a palavra” (1992-2005) - Oliveira, Leidiana Marinho Souza (2020)
The period covered by this research (from 1994 to 2005) ranges from the first survey of the Zapatista Army of National Liberation to the Sixth Lacandona Jungle Declaration, also called by the Zapatistas as “La otra campaña”. After a brief period of armament undertaken on January 1, 1994, the Zapatistas change their policies to those policies that are considered achieved beyond armed conflict. This research sought through Discourse Analysis to deepen the Zapatista speeches allocated on the official website of the EZLN, deepening the debates about the writings and historical narratives inherent to the Research Line: Ideas, Knowledge and Writings of (and in) History. As the assumptions start from the assumption that the Zapatista discourses show elements that awaken the general community to the problems related to the indigenous in Mexico, in a kind of militancy in the political field of dialogue. Using a word as a weapon, the writings of Subcomandante Marcos and the CCRI-CG (Indigenous Revolutionary Clandestine Committee - General Command) point to the construction of a Zapatista Autonomy as a form of resistance to the Mexican government.